Design and Implementation of FTTB Network Transmission in High-Rise Buildings Using GPON - Ahmad Yuhani; Emy Haryatmi; Deni Haryadi; Yunus Bakhtiar Arafat (Sultan Publisher, 2025)
The advancement of digital communication technology has significantly increased the demand for reliable network infrastructure, particularly in high-rise buildings such as hotels and resorts. This study aims to design and evaluate a Fiber To The Building (FTTB) network system based on Gigabit Passive Optical Network (GPON) technology at The Anvaya Beach Resort Bali. The system is designed to distribute integrated communication services including data voice, and video, through a zoning approach based on the functional layout of the building. The Waterfall method is employed in the system development, encompassing the stages of requirement analysis, topology design, field implementation, and optical performance testing. The findings indicate that most zones have optical attenuation values within the standard range (15–28 dB), and the received signal power remains within the acceptable threshold (-28 dBm). However, several areas exhibit suboptimal signal performance, particularly those with long distribution paths and a high number of optical splitters. Zone C1.1 demonstrates the best performance, with stable attenuation levels and signal strength within standards, without requiring additional active devices. The study concludes that a GPON-based FTTB system can efficiently and flexibly meet the data communication needs of high-rise buildings and other complex building environments with similar systems.